Optical spectroscopy and upconversion luminescence in Nd3+ doped Ga10Ge25S65 glass - Rai, Vineet Kumar; de Araujo, Cid B.; Ledemi, Y. [UNESP]; Bureau, B.; Poulain, M.; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2009)
Optical properties of a neodymium (Nd3+) doped glass having composition based on the (Ga2S3)-(GeS2) system are reported. Transition probabilities, radiative lifetimes, and branching ratios related to Nd3+ levels were determined. Frequency upconversion (UC) luminescence due to nonresonant excitation at 1064 nm was observed at approximate to 535, approximate to 600, and approximate to 670 nm. The dependence of the UC intensity on the laser intensity and on the Nd3+ concentration as well as the dynamics of the luminescence process were studied. The results indicate that two-photon absorption by isolated Nd3+ ions and energy transfer among pairs of Nd3+ ions contribute to the UC luminescence. (C) 2009 American Institute of Physics. [doi:10.1063/1.3259439]